Insect Visitors and Potential Pollinators of Orchis militaris (Orchidaceae) in Southern Belgium. Issue 1 (30th September 2016) - Henneresse, Thomas; Tyteca, Daniel
Abstract: As part of a research project on the food deception strategy in Orchis militaris (L.), the objective of this study was to identify insect visitors and potential pollinators of this orchid species in Belgium. In 2013, insects were collected over 2 d per site in five localities distributed in Southern Belgium (Wallonia). A total of 104 insects belonging to 49 species were caught. Dipterans were the most abundant visitors (50% of total specimens), followed by Hymenopterans (32%). Rhingia campestris Meigen, Bombylius venosus Mikan, Apis mellifera (L.), and Bombus lapidarius (L.) were the most abundant species. Only five specimens bore one to more than 10 pollinia: four honeybees ( A. mellifera ) and one bumblebee worker ( B. lapidarius ). These two species should be considered as potential pollinators in the study area, but probably not confirmed ones.